2005
DOI: 10.1002/adfm.200400337
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar Charge Transport in Films of Methanofullerene and Poly(phenylenevinylene)/Methanofullerene Blends

Abstract: Herein, we report experimental studies of electron and hole transport in thin films of [6,6]‐phenyl C61 butyric acid methyl ester (PCBM) and in blends of poly[2‐methoxy‐5‐(3′,7′‐dimethyloctyloxy)‐1,4‐phenylenevinylene] (MDMO‐PPV) with PCBM. The low‐field hole mobility in pristine MDMO‐PPV is of the order of 10–7 cm2 V–1 s–1, in agreement with previous studies, whereas the electron mobility in pristine PCBM was found by current‐density–voltage (J–V) measurements to be of the order of 10–2 cm2 V–1 s–1, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
210
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(238 citation statements)
references
References 62 publications
26
210
0
2
Order By: Relevance
“…In the case of PCBM, however, calculated might correspond to either electron or holes since recent reports showed that both are equally mobile [14,28]. Figure 5 shows the evolution of mobility with time and electric field, with early values ranging from 0.05 to 0:2 cm 2 =V s for the highest applied fields.…”
mentioning
confidence: 99%
“…In the case of PCBM, however, calculated might correspond to either electron or holes since recent reports showed that both are equally mobile [14,28]. Figure 5 shows the evolution of mobility with time and electric field, with early values ranging from 0.05 to 0:2 cm 2 =V s for the highest applied fields.…”
mentioning
confidence: 99%
“…However, in the presence of additional trap-assisted recombination losses, a stronger dependency of V oc on the light intensity is typically observed. In this case, the slope of V oc vs. ln(P light ) is closer to 2kT/q [58][59][60]. So a smaller slope (close to 1) means the PSC does not suffer from trap-assisted bimolecular recombination.…”
Section: Charge Transport and Recombinationmentioning
confidence: 90%
“…调节前驱体溶液的浓度和浸泡时间来控制六边 形 ZnO 纳米棒的直径和长度, 两步法工艺可以保证钙 钛矿材料充分填充于 ZnO 纳米棒之间获得 11.13%效率 的太阳电池 [87] (见图 9). 此外, 也可以通过醋酸锌的水解 作用形成 ZnO 纳米颗粒, 旋涂在 ITO 表面无需后续的烧 结过程便可获得高质量的致密的电子传输层, 通过两步 法加工钙钛矿薄膜可以制备 15.7%效率的太阳电池 [36] [73,80,93] . [40,75] .…”
Section: Yangunclassified